Adhesive, positive electrode sheet, method for manufacturing the same, battery, and power tool

CN122941328APending Publication Date: 2026-10-20TSINGHUA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611010285.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,干法高载正极在无溶剂条件下粘结剂、导电剂难以均匀分散,易形成局部团聚,难以控制电极微观结构均匀性,并且干法电极膜与集流体结合力弱,界面阻抗高,易发生脱膜,同时由于电极厚度增加导致传输动力学迟滞,离子/电子传输路径显著增长,极化现象加剧

Benefits of technology

[0021]本申请的附加方面和优点将在下面的描述中部分给出,部分将从下面的描述中变得明显,或通过本申请的实践了解到。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application discloses an adhesive, a positive electrode sheet, a method for preparing the same, a battery, and an electrical device. The adhesive is obtained through in-situ polymerization of asymmetric lithium salt monomers with double bonds and polyethylene glycol acrylate monomers. The adhesive of this application possesses high bond strength, high ionic conductivity, and excellent interfacial stability. Using this adhesive, high-load positive electrode sheets can be prepared, effectively improving the energy density, cycle performance, and rate performance of the battery, providing a novel material solution for high-performance dry-process high-load positive electrode sheets. Furthermore, the preparation method of the positive electrode sheet is simple, low-cost, compatible with existing processes, and easily scalable for industrial-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, specifically to adhesives, positive electrode sheets and their preparation methods, batteries and electrical devices. Background Technology

[0002] With the rapid development of the electric vehicle and large-scale energy storage markets, the requirements for lithium battery energy density are increasing. Developing high areal loading cathodes is one of the effective ways to improve battery energy density. Compared with traditional wet processes, dry electrode technology is considered a key direction for next-generation high-performance battery manufacturing due to its advantages such as no solvent required, low energy consumption, short process path, and suitability for thick electrode preparation. However, in dry high-load cathodes, binders and conductive agents are difficult to disperse uniformly under solvent-free conditions, easily forming local agglomerations. It is difficult to control the uniformity of the electrode microstructure. Furthermore, the dry electrode film has weak bonding force with the current collector, high interfacial impedance, and is prone to delamination. At the same time, the increased electrode thickness leads to sluggish transport kinetics, significantly increases the ion / electron transport path, and intensifies polarization. Summary of the Invention

[0003] This application aims to at least partially address one of the technical problems in related technologies. To this end, one objective of this application is to provide an adhesive, a positive electrode sheet, a method for preparing the same, a battery, and an electrical device. The adhesive of this application possesses characteristics such as high bonding strength, high ionic conductivity, and excellent interfacial stability. Using this adhesive, high-load positive electrode sheets can be prepared, effectively improving the energy density, cycle performance, and rate performance of the battery, providing a novel material solution for high-performance dry-process high-load positive electrode sheets. Furthermore, the method for preparing the positive electrode sheet is simple, easy to implement, low-cost, compatible with existing processes, and easily scalable for industrial-scale production.

[0004] In a first aspect of this application, an adhesive is proposed. According to an embodiment of this application, the adhesive is obtained by in-situ polymerization of a double-bonded asymmetric lithium salt monomer and polyethylene glycol-based acrylate monomer.

[0005] In the adhesive according to the embodiments of this application, the double-bonded asymmetric lithium salt monomer introduces double bonds and highly delocalized anions, achieving multifunctional integration of a single component. Its double bonds can copolymerize with the double bonds in the polyethylene glycol acrylate monomer to form a polymer, giving the adhesive high adhesive strength. Its highly delocalized anions can promote the efficient dissociation and transport of lithium ions, giving the adhesive intrinsic ionic conductivity. Furthermore, the anions are covalently anchored to the polymer network, significantly increasing the lithium ion transference number. The polyethylene glycol acrylate monomer has highly compliant ether bonds (-COC-), which, after copolymerization with the lithium salt monomer, can enhance the flexibility and elasticity of the polymer network, thereby improving interfacial stability. Simultaneously, its ether oxygen atom (-O-) has a lone pair of electrons, which can react with lithium ions (Li... +A weak coordination interaction occurs, thereby further enhancing lithium-ion conductivity. Thus, the synergistic effect of the double-bonded asymmetric lithium salt monomer and the polyethylene glycol-based acrylate monomer gives the adhesive high bond strength, high ionic conductivity, and excellent interfacial stability.

[0006] According to an embodiment of this application, the double-bonded asymmetric lithium salt monomer has the structure shown in formula (I): (I); R1 is selected from hydrogen or sulfonyl group; R2 is selected from cyano, C 1-6 Alkyl, Halogenated C 1-6 Alkyl, C 1-6 Alkylamino, C 6-12 Aryl, Halogenated C 6-12 Aryl, C 2-6 Cyclic ether group, ; R3 is selected from hydrogen, acyl, or sulfonyl groups; R4 is selected from hydrogen, C 1-6 Alkyl, C 1-6 Alkoxy, C 6-12 Aryl; m is an integer selected from 1 to 6.

[0007] According to embodiments of this application, the double-bonded asymmetric lithium salt monomer is obtained by reacting an amino compound, an alkenyl chloride compound, and a lithium source.

[0008] According to embodiments of this application, the amine compound is selected from one of the following: .

[0009] According to embodiments of this application, the alkenyl chloride compound is selected from one of the following: .

[0010] According to embodiments of this application, the lithium source is selected from one of the following: lithium perchlorate, lithium tetrafluoroborate, and lithium hydroxide.

[0011] According to embodiments of this application, the polyethylene glycol-based acrylate monomer has the structure shown in formula (II) or (III): (II) or (III); The molecular weight of the polyethylene glycol acrylate monomer is 200 g mol. -1 ~4000 g mol -1 .

[0012] According to an embodiment of this application, the mass ratio of the double-bonded asymmetric lithium salt monomer to the polyethylene glycol acrylate monomer is (0.1~10):1.

[0013] In a second aspect, this application provides a positive electrode sheet. According to an embodiment of this application, the positive electrode sheet includes: a current collector and a positive active material layer, the positive active material layer being located on at least one surface of the current collector, and the positive active material layer comprising a positive active material and the binder described in the first aspect. Therefore, the positive electrode sheet of this application possesses high loading capacity, high interfacial stability, and ion transport performance.

[0014] According to embodiments of this application, the double-bonded asymmetric lithium salt monomer and the polyethylene glycol acrylate monomer each independently account for 1% to 5% of the mass ratio of the positive electrode active material layer.

[0015] According to an embodiment of this application, the areal density of the positive electrode active material layer is 50 mg / cm³. 2 ~100 mg / cm 2 .

[0016] In a third aspect of this application, a method for preparing the positive electrode sheet described in the second aspect is proposed. According to an embodiment of this application, the method includes: dry mixing the positive electrode active material, a double-bonded asymmetric lithium salt monomer, polyethylene glycol acrylate monomer, and an initiator to obtain a mixture; placing the mixture on at least one surface of the current collector and performing hot pressing to form the positive electrode active material layer. Thus, the aforementioned positive electrode sheet can be obtained using this method. Furthermore, this preparation method is simple, easy to implement, low-cost, compatible with existing processes, and easily scalable for industrial-scale production.

[0017] According to embodiments of this application, the initiator includes at least one of azobisisobutyronitrile, benzoyl peroxide, and potassium persulfate.

[0018] According to embodiments of this application, the conditions for the hot pressing treatment satisfy at least one of the following: The temperature for the hot pressing process is 80℃~120℃; The pressure of the hot pressing process is 10 MPa to 20 MPa; The hot pressing process takes 10 to 30 minutes.

[0019] In a fourth aspect, this application proposes a battery comprising the binder described in the first aspect, the positive electrode sheet described in the second aspect, or the positive electrode sheet obtained by the method for preparing the positive electrode sheet described in the third aspect. Thus, the battery of this application possesses high energy density, high cycle performance, and high rate performance.

[0020] In a fifth aspect, this application proposes an electrical device. According to an embodiment of this application, the electrical device comprises: the adhesive described in the first aspect, the positive electrode sheet described in the second aspect, the positive electrode sheet obtained by the method for preparing the positive electrode sheet described in the third aspect, or the battery described in the fourth aspect. Therefore, the electrical device of this application has high-efficiency energy output and excellent service life.

[0021] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0022] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 Double-bonded asymmetric lithium salt monomers were shown. N 2 V The proton spectrum of 2; Figure 2 Double-bonded asymmetric lithium salt monomers were shown. N 2 V Fluorine spectrum of 2; Figure 3 Double-bonded asymmetric lithium salt monomers were shown. N 15 V The hydrogen spectrum of 1. Detailed Implementation

[0023] The embodiments of this application are described in detail below. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0024] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this application, unless otherwise stated, "multiple" means two or more.

[0025] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this application.

[0026] In this application, the terms "comprising" or "including" are open-ended expressions, meaning they include the content specified in this application but do not exclude other aspects.

[0027] In the absence of solvents, the binder and conductive agent in dry high-load cathodes are difficult to disperse uniformly, which easily leads to local agglomeration. It is difficult to control the uniformity of the electrode microstructure. Furthermore, the dry electrode film has weak bonding force with the current collector, high interfacial impedance, and is prone to delamination. At the same time, the increased electrode thickness leads to sluggish transport dynamics, significantly increases the ion / electron transport path, and intensifies polarization.

[0028] Currently, dry electrodes commonly use polytetrafluoroethylene (PTFE) as a binder, forming a network structure through its fibrillation to bond the active material and conductive agent. However, PTFE has many inherent drawbacks: it is an insulating material, severely hindering electron transport within the electrode; its strong hydrophobicity affects electrolyte wetting; its narrow electrochemical window makes it prone to decomposition under high voltage; and its fibrillation process is sensitive to temperature and shear force, resulting in a narrow process window and making it difficult to precisely control the electrode's microstructure.

[0029] To overcome the limitations of PTFE binders, researchers have explored strategies to replace PTFE with in-situ polymerized polymers. Theoretically, this strategy involves liquid monomers penetrating into the gaps between active materials and then polymerizing to form a more uniform three-dimensional continuous network structure, thereby improving the mechanical integrity and interfacial stability of the electrode. However, existing in-situ polymerized binders still face significant challenges: First, most polymer matrices lack efficient lithium-ion transport channels, resulting in low ionic conductivity; second, their electrochemical stability is insufficient, making it difficult to withstand the working environment of high-voltage cathode materials; furthermore, their interfacial compatibility with high-nickel cathodes and lithium metal anodes is poor, making side reactions difficult to suppress; and finally, it is often difficult to balance multiple performance requirements such as high bond strength, high ionic conductivity, and excellent interfacial stability.

[0030] Based on this, in a first aspect of this application, an adhesive is proposed. According to an embodiment of this application, the adhesive is obtained by in-situ polymerization of a double-bonded asymmetric lithium salt monomer and polyethylene glycol-based acrylate monomer.

[0031] In the adhesive according to the embodiments of this application, the double-bonded asymmetric lithium salt monomer introduces double bonds and highly delocalized anions, achieving multifunctional integration of a single component. Its double bonds can copolymerize with the double bonds in the polyethylene glycol acrylate monomer to form a polymer, giving the adhesive high adhesive strength. Its highly delocalized anions can promote the efficient dissociation and transport of lithium ions, giving the adhesive intrinsic ionic conductivity. Furthermore, the anions are covalently anchored to the polymer network, significantly increasing the lithium ion transference number. The polyethylene glycol acrylate monomer has highly compliant ether bonds (-COC-), which, after copolymerization with the lithium salt monomer, can enhance the flexibility and elasticity of the polymer network, thereby improving interfacial stability. Simultaneously, its ether oxygen atom (-O-) has a lone pair of electrons, which can react with lithium ions (Li... + A weak coordination interaction occurs, thereby further enhancing lithium-ion conductivity. Thus, the synergistic effect of the double-bonded asymmetric lithium salt monomer and the polyethylene glycol-based acrylate monomer gives the adhesive high bond strength, high ionic conductivity, and excellent interfacial stability.

[0032] In this paper, the term "asymmetric lithium salt monomer" refers to lithium salts with anionic structures exhibiting structural asymmetry, and "polyethylene glycol acrylate monomer" is used interchangeably with "PEG-based acrylate monomer".

[0033] According to an embodiment of this application, the double-bonded asymmetric lithium salt monomer has the structure shown in formula (I): (I); R1 is selected from hydrogen or sulfonyl group; R2 is selected from cyano, C 1-6 Alkyl, Halogenated C 1-6 Alkyl, C 1-6 Alkylamino, C 6-12 Aryl, Halogenated C 6-12 Aryl, C 2-6 Cyclic ether group, ; R3 is selected from hydrogen, acyl, or sulfonyl groups; R4 is selected from hydrogen, C 1-6 Alkyl, C 1-6 Alkoxy, C 6-12 Aryl; m is an integer selected from 1 to 6.

[0034] The sulfonyl group introduced into the double-bonded asymmetric lithium salt monomer exhibits a strong electron-withdrawing inductive effect, effectively dispersing and stabilizing the attached anionic charge, significantly reducing the Coulombic force between lithium ions and anions, and promoting the dissociation of the lithium salt in the polymer matrix. This is key to achieving high lithium-ion conductivity. Simultaneously, due to the highly delocalized anionic charge and structural stability, its antioxidant decomposition voltage is significantly increased (≥ 4.5 V). vs.Li + The benzene ring ( / Li) can withstand the working environment of high-voltage cathode materials and inhibit the decomposition of the binder under high voltage. As a rigid aromatic ring structure, the benzene ring, when introduced into the polymer backbone or side chains, can effectively improve the mechanical strength and modulus of the binder network, enhance the structural integrity of the electrode, and buffer the volume changes of the active material during cycling. Furthermore, the π-π conjugated system gives it high chemical and thermal stability, making it less prone to redox reactions, further consolidating the material's oxidation resistance under high voltage. At the cathode working potential, the cyclic ether groups can undergo electrochemically driven ring-opening polymerization. This "in-situ" polymerization characteristic allows it to preferentially form a uniform polymer coating layer on the surface of the cathode active particles. The ether oxygen atoms within the polyether segments can coordinate with lithium ions, providing a pathway for lithium ion transport in the interfacial film and helping to reduce interfacial impedance.

[0035] In some embodiments, C 1-6 Alkyl, Halogenated C 1-6 Alkyl, C 1-6 The number of carbon atoms in an alkylamino group can be independently 1, 2, 3, 4, 5, or 6; C 6-12 Aryl, Halogenated C 6-12 The number of carbon atoms in an aryl group can be independently 6, 7, 8, 9, 10, 11, or 12; C 2-6 The number of carbon atoms in the cyclic ether group can be 2, 3, 4, 5, or 6; m can be 1, 2, 3, 4, 5, or 6.

[0036] According to embodiments of this application, the double-bonded asymmetric lithium salt monomer is obtained by reacting an amino compound, an alkenyl chloride compound, and a lithium source. The amino group in the amino compound undergoes amidation with the acyl group in the alkenyl chloride compound via a nucleophilic substitution reaction, generating an organic anionic precursor. Subsequently, the anionic structure in this precursor (such as sulfonylimide) undergoes a neutralization or ion exchange reaction with the lithium source, whereby the lithium ion replaces the original cation, ultimately combining with the organic anion in the form of an ionic bond to form the double-bonded asymmetric lithium salt monomer.

[0037] According to embodiments of this application, the amine compound is selected from one of the following: .

[0038] Therefore, the adhesives prepared using this amine compound have high bonding strength, high ionic conductivity and excellent interfacial stability.

[0039] According to embodiments of this application, the alkenyl chloride compound is selected from one of the following: .

[0040] Therefore, the adhesive prepared using this alkenyl chloride compound has high bonding strength, high ionic conductivity and excellent interfacial stability.

[0041] According to embodiments of this application, the lithium source is selected from one of the following: lithium perchlorate, lithium tetrafluoroborate, and lithium hydroxide.

[0042] According to embodiments of this application, the polyethylene glycol-based acrylate monomer has the structure shown in formula (II) or (III): (II) or (III); The molecular weight of the polyethylene glycol acrylate monomer is 200 g mol. -1 ~4000 g mol -1 Exemplary position 200 g mol -1 500 g mol -1 1000 g mol -1 1500 g mol -1 2000 g mol -1 2500 g mol -1 3000 g mol -1 3500 g mol -1 4000 g mol -1 .

[0043] In some embodiments, the molecular weight of the structure shown in formula (II) can be 300 g mol. -1 950 g mol -1 2000 g mol -1 4000 g mol -1 The molecular weight of the structure shown in formula (II) can be 200 g mol. -1 600 g mol -1 2000 g mol -1 4000 g mol -1 .

[0044] According to embodiments of this application, the mass ratio of the double-bonded asymmetric lithium salt monomer to the polyethylene glycol-based acrylate monomer is (0.1~10):1. In some embodiments, the mass ratio of the double-bonded asymmetric lithium salt monomer to the polyethylene glycol-based acrylate monomer can be 0.1:1, 1:1, 2:1, 4:1, 5:1, 6:1, 8:1, or 10:1. This allows the adhesive to achieve both good mechanical properties and ion transport properties.

[0045] In a second aspect of this application, a positive electrode sheet is provided. According to an embodiment of this application, the positive electrode sheet includes: a current collector and a positive active material layer, the positive active material layer being located on at least one surface of the current collector, the positive active material layer including a positive active material and the adhesive described in the first aspect.

[0046] As mentioned above, the adhesive of this application has high bonding strength, enhancing the structural integrity of the electrode and the bonding force with the current collector, and exhibiting strong interfacial stability. Furthermore, the adhesive possesses ionic conductivity, improving the ion transport performance of the electrode sheet. Thus, high loading capacity is achieved on the positive electrode sheet.

[0047] According to embodiments of this application, the double-bonded asymmetric lithium salt monomer and the polyethylene glycol-based acrylate monomer each independently account for 1% to 5% of the mass ratio of the positive electrode active material layer. In some embodiments, the double-bonded asymmetric lithium salt monomer and the polyethylene glycol-based acrylate monomer each independently account for 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5% of the mass ratio of the positive electrode active material layer. This not only enables the formation of a three-dimensional continuous network with high bonding strength and good flexibility after in-situ polymerization, thereby significantly enhancing the structural integrity of the electrode and the current collector bonding force; it also improves ion transport performance, effectively reduces the bulk and interfacial impedance of thick electrodes, and forms a stable interfacial film with excellent ion conductivity on the electrode surface, synergistically improving the rate performance, cycle stability, and energy density of the battery.

[0048] According to an embodiment of this application, the areal density of the positive electrode active material layer is 50 mg / cm³. 2 ~100mg / cm 2 In some embodiments, the areal density of the positive electrode active material layer is 50 mg / cm³. 2 60mg / cm 2 70mg / cm 2 80mg / cm 2 90mg / cm 2 100mg / cm 2 Therefore, the positive electrode of this application has a high load capacity, which improves the energy density of the battery.

[0049] According to embodiments of this application, when the positive electrode sheet is used in a lithium-ion battery, the positive electrode active material can be any positive electrode active material known in the art for lithium-ion batteries. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNiO2). 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.8 Co 0.15 Al 0.05 At least one of O2 or its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate or lithium manganese iron phosphate and carbon composites.

[0050] According to embodiments of this application, when the positive electrode sheet is used in a sodium-ion battery, the positive electrode active material may include at least one of the following materials: Na x MO2, wherein M includes at least one of Ti, V, Mn, Co, Ni, Fe, Zn, V, Zr, Ce, Cr, and Cu, and 0 < x ≤ 1.

[0051] Polyanionic compounds: NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2(P2O7), NaM'PO4F (M' includes at least one of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y wherein 0≤y≤1, at least one of them.

[0052] Prussian blue analog compounds: Na a Me b Me' c (CN)6, wherein Me and Me' each independently include at least one of Ni, Cu, Fe, Mn, Co, and Zn, 0<a≤2, 0<b<1, 0<c<1.

[0053] In some embodiments, the positive electrode active material comprises Na X1 M1O2, Na X2 M2[M3(CN)6], NaFePO4, Na3V2(PO4)3, Na2M4P2O7, Na2Fe2(SO4)3, Na2M4(SO4)2·2H2O, at least one of them, wherein 0<x1≤1, M1 comprises at least one of Ni, Co, Mn, Fe and Cu, 0<x2<6, M2 comprises at least one of Ni, Fe and Mn, M3 comprises at least one of Fe and Mn, and M4 comprises at least one of Fe, Co, Mn and Cu.

[0054] In some embodiments, the positive electrode active material comprises a ternary layered sodium-based material, exemplarily, the sodium-ion battery comprises NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, NaNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2(NMC), Na3V2(PO4)3(NMN), Na 0.9 Mn 0.6 Fe 0.4 PO4(NMFP), sodium iron phosphate pyrophosphate Na4Fe3(PO4)2(P2O7) and sodium ferrocyanide, one of them.

[0055] According to embodiments of this application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0056] According to embodiments of this application, the positive electrode active material layer may optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0057] In a third aspect of this application, a method for preparing the positive electrode sheet described in the second aspect is provided. According to an embodiment of this application, the method includes: dry mixing the positive electrode active material, a double-bond asymmetric lithium salt monomer, polyethylene glycol acrylate monomer, and an initiator to obtain a mixture; placing the mixture on at least one surface of the current collector and performing hot pressing to form the positive electrode active material layer.

[0058] First, a dry-mixing process is used to uniformly disperse the positive electrode active material, double-bond asymmetric lithium salt monomer, polyethylene glycol acrylate monomer, and initiator, allowing the monomers to penetrate into the gaps between the active materials. Next, a hot-pressing process is performed. Under the action of the initiator, the double bonds of the double-bond asymmetric lithium salt monomer and the double bonds of the polyethylene glycol acrylate monomer undergo a copolymerization reaction, forming an in-situ polymer binder. This firmly fixes the positive electrode active material to the current collector surface, resulting in the positive electrode sheet. The characteristics and advantages described above for the positive electrode sheet also apply to this preparation method and will not be repeated here. Furthermore, this preparation method is simple, easy to implement, low-cost, compatible with existing processes, and easily scalable for industrial-scale production.

[0059] According to embodiments of this application, the initiator includes at least one of azobisisobutyronitrile, benzoyl peroxide, and potassium persulfate.

[0060] According to embodiments of this application, the conditions for the hot pressing treatment satisfy at least one of the following: The hot pressing temperature is 80℃~120℃, exemplarily 80℃, 90℃, 100℃, 110℃, 120℃; The pressure of the hot pressing process is 10 MPa to 20 MPa, and exemplary values ​​are 10 MPa, 12 MPa, 14 MPa, 15 MPa, 16 MPa, 18 MPa, and 20 MPa. The hot pressing treatment time is 10 min to 30 min, for example 10 min, 15 min, 20 min, 25 min, and 30 min.

[0061] Using the above-mentioned hot-pressing conditions is beneficial for obtaining adhesives that combine high bonding strength, ionic conductivity, and interfacial stability.

[0062] According to embodiments of this application, the double-bonded asymmetric lithium salt monomer is obtained by reacting an amino compound, an alkenyl chloride compound, and a lithium source. The amino group in the amino compound undergoes amidation with the acyl group in the alkenyl chloride compound via a nucleophilic substitution reaction, generating an organic anionic precursor. Subsequently, the anionic structure in this precursor (such as sulfonylimide) undergoes a neutralization or ion exchange reaction with the lithium source, whereby the lithium ion replaces the original cation, ultimately combining with the organic anion in the form of an ionic bond to form the double-bonded asymmetric lithium salt monomer.

[0063] According to an embodiment of this application, the reaction conditions include: adding an amino compound to a container and dissolving it with anhydrous acetonitrile. Then, anhydrous potassium carbonate is added, and the mixture is stirred at 0-4°C for 1-3 hours. The alkenyl chloride compound is dissolved in anhydrous acetonitrile and added dropwise to the dissolved mixture. After the addition is complete, the mixture is stirred at 0-4°C for 20-40 min and then at room temperature for 36-60 h. After filtering to remove insoluble solids, the filtrate is concentrated by rotary evaporation to obtain the product. The product is then washed with diethyl ether to remove impurities, filtered to obtain a filter cake, and dried under vacuum after at least one rinsing to obtain the potassium salt. The synthesized potassium salt and lithium salt are dissolved in anhydrous acetonitrile and reacted for 20-30 h. The precipitate is then filtered, and the filtrate is concentrated by rotary evaporation to obtain a solid. After vacuum freeze-drying, a double-bonded asymmetric lithium salt monomer is obtained.

[0064] In a fourth aspect, this application proposes a battery comprising the binder described in the first aspect, the positive electrode sheet described in the second aspect, or the positive electrode sheet obtained by the method for preparing the positive electrode sheet described in the third aspect. Thus, the battery of this application possesses high energy density, high cycle performance, and high rate performance.

[0065] According to embodiments of this application, the battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. During battery charging and discharging, active ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator is disposed between the positive and negative electrodes, primarily to prevent short circuits between the positive and negative electrodes, while simultaneously allowing ions to pass through.

[0066] According to an embodiment of this application, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side surface of the negative current collector, the negative active material layer including a negative active material.

[0067] According to embodiments of this application, the negative electrode current collector can be a metal foil or a composite current collector. For example, copper foil can be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0068] According to embodiments of this application, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. Silicon-based materials may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include at least one of elemental tin, tin oxide compounds, and tin alloys.

[0069] According to embodiments of this application, the negative electrode active material layer may optionally include a negative electrode binder. The negative electrode binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0070] According to embodiments of this application, the negative electrode active material layer may optionally include a negative electrode conductive agent. The negative electrode conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0071] According to embodiments of this application, the negative electrode active material layer may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0072] According to embodiments of this application, a negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet (e.g., negative electrode active material, negative electrode conductive agent, negative electrode binder and any other components) in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0073] This application does not impose any particular limitation on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected. According to embodiments of this application, the separator membrane material may include at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, or polyvinylidene fluoride.

[0074] This application does not impose any particular limitation on the type of electrolyte, which may include electrolyte salts and solvents. Exemplarily, electrolyte salts include lithium hexafluorophosphate / sodium (Li / NaPF6), lithium hexafluoroantimonyate / sodium (Li / NaAsF6), lithium perchlorate / sodium (Li / NaClO4), lithium tetrafluoroborate / sodium (Li / NaBF4), lithium hexafluoroacetylacetonate / sodium (Li / NaDFH), lithium bis(oxalate-borate) / sodium (Li / NaBOB), lithium trifluoromethanesulfonylimide / sodium (Li / NaTFSI), and lithium difluorooxalate-borate / sodium (Li / N... At least one of aDFOB and lithium / sodium bis(difluorosulfonyl)imide (Li / NaFSI); the organic solvent includes at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), acetonitrile (ACN), fluoroethylene carbonate (FEC), vinylene carbonate (VC), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), ethyl methyl carbonate (EMC), propylene carbonate (PC), methylpyrrolidone (NMP), tetrahydrofuran (THF), and 1,2-dimethoxyethane (DME).

[0075] According to embodiments of this application, the battery may include an outer packaging. This outer packaging is used to encapsulate the positive electrode, the negative electrode, and the electrolyte.

[0076] According to embodiments of this application, the outer packaging may include a shell and a cover. The shell may include a bottom plate and side plates connected to the bottom plate, the bottom plate and side plates forming a receiving cavity. The shell has an opening communicating with the receiving cavity, and the cover can be placed over the opening to close the receiving cavity.

[0077] According to embodiments of this application, the outer packaging of the battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.

[0078] The outer packaging of batteries can also be a soft pack, such as a pouch. The material of the soft pack can be aluminum-plastic film, etc.

[0079] The battery of this application may be in the form of a battery cell, a battery module, or a battery pack. A battery cell includes a casing, an electrode core, and an electrolyte. The casing forms an accommodating space, and the electrode core and electrolyte are disposed within the accommodating space. The electrode core may include a positive electrode, a negative electrode, and a separator, which are arranged in a stacked or wound manner. In some embodiments, battery cells can be assembled into a battery module. A battery module may contain one or more battery cells, and a battery pack may contain one or more batteries. The specific number can be selected by those skilled in the art based on the application and capacity of the battery module.

[0080] In a fifth aspect, this application proposes an electrical device. According to an embodiment of this application, the electrical device comprises: the adhesive described in the first aspect, the positive electrode sheet described in the second aspect, the positive electrode sheet obtained by the method for preparing the positive electrode sheet described in the third aspect, or the battery described in the fourth aspect. Thus, the electrical device of this application exhibits high-efficiency energy output and excellent service life.

[0081] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices can include, but are not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, energy storage systems, etc.

[0082] As an electrical device, you can choose individual battery cells, battery modules, or battery packs according to your usage requirements.

[0083] As one example, the electrical device can be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the battery for this electrical device, a battery pack or battery module can be used.

[0084] Another example of the device could be a mobile phone, tablet computer, laptop computer, etc. This device typically requires a slim and lightweight design and can use a single battery cell as its power source.

[0085] The following will explain the solution of this application with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0086] Amine compounds:

[0087] alkenyl chloride compounds:

[0088] PEG-based acrylate monomers:

[0089] Preparation Example Prepare double-bonded asymmetric lithium salt monomers using the following methods. N 2 V 2. N 6V 2. N 15 V 1. N 2 V 3. N 5 V 5. N 7 V 4. N 2 V 5. N 11 V 5. N 13 V 4. N 14 V 2: A 100 mL three-necked flask was purged three times with vacuum and argon using a double-row tube. 10 mmol of the amine monomer was added, followed by 40 mL of anhydrous acetonitrile, and the mixture was stirred for 30 min to dissolve. Then, 2.0 eq of anhydrous potassium carbonate (20 mmol) was added, and the mixture was stirred at 0 °C for 1 h. 1.01 eq of the alkenyl chloride compound (10.01 mmol) was dissolved in 10 mL of anhydrous acetonitrile and added dropwise to the cooled mixture through a constant-pressure dropping funnel. After the addition was complete, the mixture was stirred at 0 °C for another 30 min, followed by stirring at room temperature for 48 h. After filtering to remove insoluble solids, the filtrate was rotary evaporated under vacuum at 60 °C to obtain the product. The product was washed with diethyl ether to remove impurities, filtered to obtain a filter cake, and after multiple washes, dried under vacuum at 80 °C for 24 h to obtain the double-bonded asymmetric lithium salt monomer.

[0090] The synthesized products were identified by NMR spectroscopy, and all were confirmed to be the target double-bond asymmetric lithium salt monomer. An example of a double-bond asymmetric lithium salt monomer is provided. N 2 V 2 and N 15 V NMR data for 1: N 2 V 2: For example Figure 1 As shown, the ¹H NMR (400 MHz, DMSO-d⁶) δ values ​​are 7.42–7.32 (m, 3H), 5.88–5.73 (m, 1H), 5.27–5.18 (m, 2H), and 3.71 (d, J=7.2 Hz, 2H). Figure 2 As shown, 19F NMR (376 MHz, DMSO-d6) δ -109.06, -109.10 (d, J=10.3 Hz).

[0091] N 15 V 1: For example Figure 3 As shown, 1H NMR (400 MHz, DMSO-d6) δ 6.73 (dd, J = 16.6, 9.9Hz, 1H), 5.97-5.69 (m, 2H).

[0092] Example 1 In this embodiment, the in-situ polymerized binder dry-process cathode (DPC-1) was prepared according to the following method, all of which were performed in a glove box: 1. In a 20 mL glass vial, add the lithium salt monomer with the double bond asymmetric structure from the preparation example in a mass ratio of 3:3:0.1:90:2:2. N 2 V 2. PEG-based acrylate monomers M 8 and azobisisobutyronitrile (AIBN) were mixed evenly, and then NCM811, conductive carbon black SP and multi-arm carbon nanotubes (CNT) were added and dispersed evenly by a high-speed shearing machine.

[0093] 2. Weigh the powder that has been mixed evenly in the previous step, press it into shape using a cold press at 10 MPa, and then press it onto aluminum foil using a hot press (100℃, 15 MPa, and 20 min) to form the positive electrode active material layer, thereby obtaining an in-situ polymer binder dry high-load positive electrode with an areal density of 100 mg / cm³. 2 .

[0094] Lithium salt monomers with double bond asymmetric structure in the positive electrode active material layer N 2 V 2. The content is 3 wt%, PEG-based acrylate monomer. M The content of 8 is 3 wt%. The dry-process high-load positive electrode with in-situ polymerized binder has a smooth and uniform appearance, without cracks or burrs.

[0095] Example 2 In this embodiment, the in-situ polymerized binder dry high-load cathode (DPC-2) was prepared according to the following method, all of which were performed in a glove box: 1. In a 20 mL glass vial, add the lithium salt monomer with the double bond asymmetric structure from the preparation example in a mass ratio of 1:5:0.1:90:2:2. N 6 V 2. PEG-based acrylate monomers M 8 and azobisisobutyronitrile (AIBN) were mixed evenly, and then NCM811, conductive carbon black SP and multi-arm carbon nanotubes (CNT) were added and dispersed evenly by a high-speed shearing machine.

[0096] 2. Weigh the powder that has been mixed evenly in the previous step, press it into shape using a cold press at 10 MPa, and then press it onto aluminum foil using a hot press (100℃, 20 MPa, and 10 min) to form the positive electrode active material layer, thereby obtaining an in-situ polymer binder dry high-load positive electrode with an areal density of 80 mg / cm³. 2 .

[0097] Lithium salt monomers with double bond asymmetric structure in the positive electrode active material layer N 6 V 2. The content is 1 wt%, PEG-based acrylate monomer. M The content of 8 is 5 wt%. The dry-process high-load positive electrode with in-situ polymerized binder has a smooth and uniform appearance, without cracks or burrs.

[0098] Example 3 In this embodiment, the in-situ polymerized binder dry high-load cathode (DPC-3) was prepared according to the following method, all of which were performed in a glove box: 1. In a 20 mL glass vial, add the lithium salt monomer with the double bond asymmetric structure from the preparation example in a mass ratio of 5:1:0.1:90:2:2. N 15 V 1. PEG-based acrylate monomers M 8 and azobisisobutyronitrile (AIBN) were mixed evenly, and then NCM811, conductive carbon black SP and multi-arm carbon nanotubes (CNT) were added and dispersed evenly by a high-speed shearing machine.

[0099] 2. Weigh the powder that has been mixed evenly in the previous step, press it into shape using a cold press at 10 MPa, and then press it onto aluminum foil using a hot press (120℃, 10 MPa, and 10 min) to form the positive electrode active material layer, thereby obtaining an in-situ polymer binder dry high-load positive electrode with an areal density of 50 mg / cm³. 2 .

[0100] Lithium salt monomers with double bond asymmetric structure in the positive electrode active material layer N 15 V 1. Content of 5 wt%, PEG-based acrylate monomer M The content of 8 is 1 wt%. The dry-process high-load positive electrode with in-situ polymerized binder has a smooth and uniform appearance, without cracks or burrs.

[0101] Example 4 The in-situ polymerized binder dry-process cathode (DPC-4) was prepared according to the method of Example 1, except that the double-bonded asymmetric lithium salt monomer of Example 1 was used instead.N 2 V 2 is replaced with the double-bonded asymmetric lithium salt monomer from Preparation Example 4. N 2 V 3. PEG-based acrylate monomers M 8 replaced with PEG-based acrylate monomers M 1.

[0102] Example 5 The in-situ polymerized binder dry-process cathode (DPC-5) was prepared according to the method of Example 1, except that the double-bonded asymmetric lithium salt monomer of Example 1 was used instead. N 2 V 2 is replaced with the double-bonded asymmetric lithium salt monomer from Preparation Example 5. N 2 V 5. Add PEG-based acrylate monomers M 8 replaced with PEG-based acrylate monomers M 2.

[0103] Example 6 The in-situ polymerized binder dry-process cathode (DPC-6) was prepared according to the method of Example 1, except that the double-bonded asymmetric lithium salt monomer of Example 1 was used instead. N 2 V 2 is replaced with the double-bonded asymmetric lithium salt monomer of Preparation Example 6. N 7 V 4. Add PEG-based acrylate monomers M 8 replaced with PEG-based acrylate monomers M 6.

[0104] Example 7 The in-situ polymerized binder dry-process cathode (DPC-7) was prepared according to the method of Example 1, except that the double-bonded asymmetric lithium salt monomer of Example 1 was used instead. N 2 V 2 is replaced with the double-bonded asymmetric lithium salt monomer from Preparation Example 7. N 2 V 5. Add PEG-based acrylate monomers M 8 replaced with PEG-based acrylate monomers M 4.

[0105] Example 8 The in-situ polymerized binder dry-process cathode (DPC-8) was prepared according to the method of Example 1, except that the double-bonded asymmetric lithium salt monomer of Example 1 was used instead. N 2 V2 is replaced with the double-bonded asymmetric lithium salt monomer of Preparation Example 8. N 11 V 5. Add PEG-based acrylate monomers M 8 replaced with PEG-based acrylate monomers M 6.

[0106] Example 9 The in-situ polymerized binder dry-process cathode (DPC-9) was prepared according to the method of Example 1, except that the double-bonded asymmetric lithium salt monomer of Example 1 was used instead. N 2 V 2 is replaced with the double-bonded asymmetric lithium salt monomer of Preparation Example 9. N 13 V 4. Add PEG-based acrylate monomers M 8 replaced with PEG-based acrylate monomers M 3.

[0107] Example 10 The in-situ polymerized binder dry-process cathode (DPC-10) was prepared according to the method of Example 1, except that the double-bonded asymmetric lithium salt monomer of Example 1 was used instead. N 2 V 2 is replaced with the double-bonded asymmetric lithium salt monomer of Preparation Example 10. N 14 V 2. PEG-based acrylate monomers M 8 replaced with PEG-based acrylate monomers M 4.

[0108] Comparative Example 1 The positive electrode was prepared according to the method of Example 1, except that in step 1, no lithium salt monomer with double bond asymmetric structure was added.

[0109] Comparative Example 2 The positive electrode sheet was prepared according to the method of Example 1, except that PEG-based acrylate monomers were not added in step 1.

[0110] Test case The ionic conductivity of the positive electrode sheets prepared in each embodiment and comparative example was tested respectively: A 12 mm diameter circular positive electrode was used as the working electrode, and a 16 mm diameter, 450 μm thick lithium metal electrode was used as the reference electrode. A PP2500 separator was used, and 100 μL of electrolyte (containing 1.0 M LiPF6 and 10% FEC, with EC, DEC, and DMC as solvents in a 1:1:1 volume ratio) was added. The electrolyte was then encapsulated in a 2032-type coin cell. Room temperature impedance testing was then performed, and the ionic conductivity (σ) was calculated using the formula. The contact area (S) between the diaphragm and the steel sheet is 1.96 cm². -2 .

[0111] The membrane thickness (L) is 25 μm.

[0112] The formula for calculating ionic conductivity is: .

[0113] The results are shown in Table 1. It can be seen that, compared with Comparative Examples 1-2, the adhesives obtained by in-situ polymerization of double bond asymmetric lithium salt monomers and PEG-based acrylate monomers in Examples 1-10 have higher peel strength and better ionic conductivity of the positive electrode sheet.

[0114] Comparative Example 1 did not add a lithium salt monomer with a double-bond asymmetric structure, but only used PEG-based acrylate monomers. While PEG segments possess lithium-ion coordination ability, they do not inherently provide freely moving lithium ions. The lack of a lithium salt monomer means the polymer network lacks a built-in lithium-ion source and an efficient anion-stabilizing structure, thus failing to form continuous ion transport channels. The ether bond (-COC-) of the PEG segments has a narrow electrochemical stability window, especially at high voltages (>4.3 V). vs. Li + Under Li conditions, PEG-based polymers are prone to oxidative decomposition. Furthermore, pure PEG-based polymers lack sufficient mechanical properties to effectively maintain the integrity of the electrode structure, easily leading to the shedding of active materials.

[0115] Comparative Example 2, without the addition of PEG-based acrylate monomers and using only lithium salt monomers with a double-bond asymmetric structure, yielded a lithium-rich salt material that was excessively rigid, brittle, and difficult to process. Although the lithium salt monomers provided abundant lithium-ion sources and transport sites, the ether oxygen atoms in the PEG segments could promote the dissociation and local migration of lithium ions. The completely rigid network would restrict segment movement, potentially hindering long-range ion migration and reducing intrinsic ionic conductivity.

[0116] Table 1

[0117] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. An adhesive, characterized in that, The adhesive is obtained by in-situ polymerization of double-bonded asymmetric lithium salt monomers and polyethylene glycol-based acrylate monomers.

2. The adhesive according to claim 1, characterized in that, The double-bonded asymmetric lithium salt monomer has the structure shown in formula (I): (I); R1 is selected from hydrogen or sulfonyl group; R2 is selected from cyano, C 1-6 Alkyl, Halogenated C 1-6 Alkyl, C 1-6 Alkylamino, C 6-12 Aryl, Halogenated C 6-12 Aryl, C 2-6 Cyclic ether group, ; R3 is selected from hydrogen, acyl, or sulfonyl groups; R4 is selected from hydrogen, C 1-6 Alkyl, C 1-6 Alkoxy, C 6-12 Aryl; m is an integer selected from 1 to 6; And / or, the polyethylene glycol-based acrylate monomer has the structure shown in formula (II) or (III): (II) or (III); And / or, the molecular weight of the polyethylene glycol acrylate monomer is 200 g mol. -1 ~4000 g mol -1 ; And / or, the mass ratio of the double-bonded asymmetric lithium salt monomer to the polyethylene glycol acrylate monomer is (0.1~10):

1.

3. The adhesive according to claim 1 or 2, characterized in that, The double-bonded asymmetric lithium salt monomer is obtained by reacting an amino compound, an alkenyl chloride compound, and a lithium source.

4. The adhesive according to claim 3, characterized in that, The amino compound is selected from one of the following: ; The alkenyl chloride compound is selected from one of the following: ; The lithium source is selected from one of the following: lithium perchlorate, lithium tetrafluoroborate, and lithium hydroxide.

5. A positive electrode sheet, characterized in that, include: A current collector and a positive electrode active material layer, the positive electrode active material layer being located on at least one side surface of the current collector, the positive electrode active material layer comprising a positive electrode active material and an adhesive as described in any one of claims 1-8.

6. The positive electrode sheet according to claim 5, characterized in that, The double-bonded asymmetric lithium salt monomer and the polyethylene glycol acrylate monomer each independently account for 1% to 5% of the mass ratio of the positive electrode active material layer; And / or, the areal density of the positive electrode active material layer is 50 mg / cm³. 2 ~100 mg / cm 2 .

7. A method for preparing the positive electrode sheet according to claim 5 or 6, characterized in that, include: The positive electrode active material, double bond asymmetric lithium salt monomer, polyethylene glycol acrylate monomer, and initiator are dry-mixed to obtain a mixture. The mixture is placed on at least one surface of the current collector and subjected to hot pressing to form the positive electrode active material layer.

8. The method according to claim 7, characterized in that, The initiator includes at least one of azobisisobutyronitrile, benzoyl peroxide, and potassium persulfate. The hot pressing treatment conditions satisfy at least one of the following: The temperature for the hot pressing process is 80℃~120℃; The pressure of the hot pressing process is 10 MPa to 20 MPa; The hot pressing process takes 10 to 30 minutes.

9. A battery, characterized in that, The positive electrode sheet includes the adhesive as described in any one of claims 1 to 4, the positive electrode sheet as described in any one of claims 5 or 6, or the positive electrode sheet prepared by the method described in claim 7 or 8.

10. An electrical device, characterized in that, The positive electrode includes the adhesive according to any one of claims 1 to 4, the positive electrode sheet according to claim 5 or 6, or the positive electrode sheet obtained by the method for preparing the positive electrode sheet according to claim 7 or 8, or the battery according to claim 9.